Twenty three years of cardiac surgery in adults with congenital heart disease - Alfredo Naranjo Ugalde; Eugenio Selman-Housein Sosa; Luis Marcano Sanz; Katia Rivera Ladino; Eutivides Aguilera Sánchez; Francisco Carballés García (ECIMED, 2012)
Introduction Prevalence of adults with congenital heart disease is changing. Most surviving patients from surgical or interventional treatment present sequels and residual lesions or complications, which could progress during adult life, and there is still another population that receives for first time surgical treatment in adult life. We analyze our experience in 23 years of surgical treatment of adult. Method A descriptive study with transversal cut was conducted, which included those adults patients operated on congenital heart disease. The patients were divided in two period of time: 1987 to 1999 and 2000 to 2010. Patients were divided in two group: those receive for first time the operation (Group I), and those that received surgery treatment during infancy (Group II). Results were analyzed in percentage and were presented in tables and a graphic. Result Tetralogy of Fallot was the congenital heart disease more frequent. Surgery strategy for Group I was corrective in 91,3 %, in the Group II was the surgery for sequel residual lesions. Survival were 72,2 % and 94,2 % in first and second period respectively. The survival was highest in the first group. Conclusions Second period of time the percentage of patient were highest and re operation for sequels or residual lesions. The surveillance has been improved in two decades of work. Key words:Congenital heart disease, surgical treatment, adults.